Ag-Hybridized plasmonic Au-triangular nanoplates: highly sensitive photoacoustic/Raman evaluation and improved antibacterial/photothermal combination therapy. Issue 18 (20th April 2018) - Peng, Ya; Liu, Yu; Lu, Xiaolin; Wang, Shouju; Chen, Maomao; Huang, Wenchao; Wu, Zhiyou; Lu, Guangming; Nie, Liming
Abstract : Core–shell metal nanostructures with versatile functions have attracted extensive attention and are highly desirable for imaging and therapeutic purposes. Abstract : Core–shell metal nanostructures with versatile functions have attracted extensive attention and are highly desirable for imaging and therapeutic purposes. Among them, gold and silver nanomaterials are widely explored for biological applications due to their unique properties. Despite a wide range of applications, limited enhancement ability and insufficient photothermal performance have hampered their further development. In this work, a novel multifunctional nanoprobe, a Au@Ag nanoplate (NP), is fabricated with a biocompatible surface in the aqueous phase. The as-obtained nanocomposite possesses a unique core–shell triangular configuration, sharp apexes, and a large specific surface area, exhibiting strong absorption at 780 nm. PEG–Au@Ag NPs depict highly sensitive photoacoustic imaging (PAI) capacity and extraordinary photothermal conversion efficiency ( η = 73%) under 808 nm laser irradiation. Raman signals are multiplied benefitting from the enhanced surface plasma resonance contributed by the silver layer and sharp spears. PAI provides deeper pathological information while Raman detection presents superficial optical properties. Their union forms comprehensive scale coverage for disease imaging and localization. Outstanding photothermal therapy and antibacterial efficacy are observed on animal disease models. This novel multifunctional nanocomposite not only holds great potential as an excellent contrast agent for the combination of PAI and Raman evaluation, but also allows tumor and infection therapy as well as the corresponding therapeutic monitoring.